The evaluation of program death 1 (PD-1) and PD-1 ligand (PD-L1) expressions in histological subtypes of primary extranodal non-hodgkin lymphoma - Farhana Mohammad Mohaidin,; Pavitratha Puspanathan,; Nur Asyilla Che Jalil,; Faezahtul Arbaeyah Hussain, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Programmed death 1 (PD-1) protein and its ligands, PD-L1 are two proteins that have been widely studied in many solid tumours. However, only limited observations were made in lymphomas, which were mainly Hodgkin lymphomas. We aimed to evaluate the expressions of PD-1 in the tumour microenvironment and PD-L1 in the tumour cells of primary extranodal non-Hodgkin lymphoma (peNHL). A cross-sectional study using 87 archived formalin-fixed paraffin-embedded tissue blocks from patients diagnosed with peNHL. Immunohistochemistry stainings for PD-1 and PD-L1 were done. The protein expressions were evaluated microscopically. The association between expressions of the PD-1 and PD-L1 with the histological subtypes of peNHL were statistically analysed. 46 (52.9%) of the cases had a negative expression of PD-L1 in the tumour cells and 57 (65.5%) had positive PD-1 expression in the tumour microenvironment. Significant associations were found between PD-1 and PD-L1 expressions with subtypes of peNHL (p<0.05). Positive expressions of both proteins were found in diffuse large B cell lymphoma (DLBCL). Our study explored the expressions of PD-1 and PD-L1 in peNHL that has demonstrated a significant association of PD-1 and PD-L1 expressions with subtypes of peNHL, which may provide additional information to the future study of these proteins.